Mutual exclusion of locally byzantine processes - Beauquier, J. (Workshop on the Future Trends of Distributed Computing Systems in the 1990s: Proceedings, 1988)
A solution of the mutual exclusion problem for processes that can have byzantine behavior, except for particular sections of their code, is presented. The problem is to design a protocol to ensure that, at a given time, no more than one process is executing in its own critical section. The protocol must yield some fairness, absence of starvation, and deadlock requirements. It is assumed that distributed processes can become faulty in all parts of their code except a special reduced part. It is asserted that this assumption makes a solution to the problem possible.< >